2008
DOI: 10.1007/bf03175554
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of seaweeds extracts against multiresistant pathogens

Abstract: Fourteen seaweeds collected from the intertidal zone of Southwest coast of India were tested against ten human pathogen bacteria and one human pathogen fungus using the well diffusion test in the casitone agar medium. The species used in the present study include five Chlorophyta (Bryopsis plumosa, Ulva fasciata, Acrosiphonia orientalis, Chaetomorpha antennina, Grateloupia filicina), five Rhodophyta (Hypnea pannosa, Gracilaria corticata, Centroceras clavulatum, Portieria hornemannii, Cheilosporum spectabile) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 20 publications
(20 reference statements)
3
68
1
1
Order By: Relevance
“…The mechanism of antibiosis of the soap samples was calculated using the ratio of MBC or MIC or MIC index as described by Shanmughapriya et al (2008) to elucidate whether the observed antibacterial effects were bactericidal or bacteriostatic. Although antimicrobials are usually regarded as bactericidal if the MBC is no more than four times the MIC (French 2006), when the ratio of MBC or MIC was ≤ 2.0, the soap samples were considered bactericidal or otherwise bacteriostatic.…”
Section: Determination Of Mechanisms Of Antibiosis (Bactericidal or Bmentioning
confidence: 99%
“…The mechanism of antibiosis of the soap samples was calculated using the ratio of MBC or MIC or MIC index as described by Shanmughapriya et al (2008) to elucidate whether the observed antibacterial effects were bactericidal or bacteriostatic. Although antimicrobials are usually regarded as bactericidal if the MBC is no more than four times the MIC (French 2006), when the ratio of MBC or MIC was ≤ 2.0, the soap samples were considered bactericidal or otherwise bacteriostatic.…”
Section: Determination Of Mechanisms Of Antibiosis (Bactericidal or Bmentioning
confidence: 99%
“…The mechanism of antibiosis of the extract was calculated using the ratio of MBC/MIC or MFC/MIC or MIC index as described by Shanmughapriya et al (2008) to elucidate whether the observed antibacterial effects were bactericidal or bacteriostatic. When the ratio of MBC/MIC or MFC/MIC was ≤ 2.0, the extract was considered bactericidal/fungicidal or otherwise bacteriostatic/fungistatic.…”
Section: Determination Of Mechanisms Of Antibiosis (Bactericidal or Bmentioning
confidence: 99%
“…If ratio of MBC/MIC was d" 2, the active crude extract was considered as bactericidal; if not, it was considered as bacteriostatic. If the ratio was e"16, then the active crude extract is considered to be ineffective 22 .…”
Section: Determination Of Minimum Bactericidal Concentrations (Mbc)mentioning
confidence: 99%